Charter of civil society for the Caribbean Community (Caribbean Community Secretariat GeorgetownGY, 1997)
Deals with aspects such as respect for fundamental civil, political, economic, social and cultural rights; the rights of women and children; respect for religious diversity; and, greater accountability and transparency in government.
Available in print and CDRom versions\n